2010
DOI: 10.1105/tpc.109.071399
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of DNA-Whirly Complexes and Their Role in Arabidopsis Organelle Genome Repair  

Abstract: DNA double-strand breaks are highly detrimental to all organisms and need to be quickly and accurately repaired. Although several proteins are known to maintain plastid and mitochondrial genome stability in plants, little is known about the mechanisms of DNA repair in these organelles and the roles of specific proteins. Here, using ciprofloxacin as a DNA damaging agent specific to the organelles, we show that plastids and mitochondria can repair DNA double-strand breaks through an error-prone pathway similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
200
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(218 citation statements)
references
References 81 publications
17
200
1
Order By: Relevance
“…The crystal structures of the Solanum tuberosum (potato) WHY1 and WHY2 proteins were solved in the free form (Desveaux et al, 2002;Cappadocia et al, 2008Cappadocia et al, , 2010. These structures revealed that both chloroplast-directed and mitochondria-directed Whirly proteins assemble into tetramers with C4 symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The crystal structures of the Solanum tuberosum (potato) WHY1 and WHY2 proteins were solved in the free form (Desveaux et al, 2002;Cappadocia et al, 2008Cappadocia et al, , 2010. These structures revealed that both chloroplast-directed and mitochondria-directed Whirly proteins assemble into tetramers with C4 symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the treatment of Arabidopsis plants with ciprofloxacin, an inhibitor of DNA gyrases that induces DSBs in both plastids and mitochondria (Rowan et al, 2010;Parent et al, 2011), results in an increase in microhomologymediated DNA rearrangements in the plastids of plants lacking WHY1 and WHY3 (Cappadocia et al, 2010). WHY2, the Whirly protein directed to mitochondria in Arabidopsis, also appears to be involved in repressing the MMBIR pathway in the mitochondria, although to a lesser extent (Cappadocia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of the crystal structure of WHIRLY proteins revealed that they form tetramers [68] and that these tetramers can also assemble into 24-mers [69,70]. The 24-oligomers of WHIRLY1 have been isolated from chloroplasts [70] and they are likely to be the structures that bind to the thylakoids.…”
Section: The Whirly Family Of Proteinsmentioning
confidence: 99%